The economic costs of malaria in four Kenyan districts: do household costs differ by disease endemicity? - Okungu Vincent; Chuma Jane; Molyneux Catherine (Malaria Journal, 2010)
Abstract Background Malaria inflicts significant costs on households and on the economy of malaria endemic countries. There is also evidence that the economic burden is higher among the poorest in a population, and that cost burdens differ significantly between wet and dry seasons. What is not clear is whether, and how, the economic burden of malaria differs by disease endemicity. The need to account for geographical and epidemiological differences in the estimation of the social and economic burden of malaria is well recognized, but there is limited data, if any, to support this argument. This study sought to contribute towards filling this gap by comparing malaria cost burdens in four Kenyan districts of different endemicity. Methods A cross-sectional household survey was conducted during the peak malaria transmission season in the poorest areas in four Kenyan districts with differing malaria transmission patterns (n = 179 households in Bondo; 205 Gucha; 184 Kwale; 141 Makueni). Findings There were significant differences in duration of fever, perception of fever severity and cost burdens. Fever episodes among adults and children over five years in Gucha and Makueni districts (highland endemic and low acute transmission districts respectively) lasted significantly longer than episodes reported in Bondo and Kwale districts (high perennial transmission and seasonal, intense transmission, respectively). Perceptions of illness severity also differed between districts: fevers reported among older children and adults in Gucha and Makueni districts were reported as severe compared to those reported in the other districts. Indirect and total costs differed significantly between districts but differences in direct costs were not significant. Total household costs were highest in Makueni (US$ 19.6 per month) and lowest in Bondo (US$ 9.2 per month). Conclusions Cost burdens are the product of complex relationships between social, economic and epidemiological factors. The cost data presented in this study reflect transmission patterns in the four districts, suggesting that a relationship between costs burdens and the nature of transmission might exist, and that the same warrants more attention from researchers and policy makers.